Pengembangan Lembar Kerja Peserta Didik (LKPD) Berorientasi POE (Predict, Observe, Explain) untuk Meningkatkan Kemampuan Berpikir Tingkat Tinggi (HOT) Siswa Kelas IV Sekolah Dasar - Sobirin; Irwan Koto; Bambang Parmadi (Jurnal Kajian Pendidikan Dasar, 2024)
This study aims to Produce Predict-Observe-Explain (POE) oriented worksheets to improve the high-level thinking skills of grade IV elementary school students. This type of research is Research and Development (R&D). The research subjects were fourth grade students at SD Negeri Kuto Tanjung. The feasibility of POE-oriented LKPD is based on the validation results that have been carried out by experts on the material, media and language aspects of predict-observe-explain (POE) oriented LKPD. In the material aspect, it is declared very feasible at 0.86. In the media aspect, it is declared very feasible at 0.85. In the language aspect, it is declared very feasible at 0.86. So that the predict-observe-explain (POE) oriented LKPD on the source material is feasible for use in learning activities. Based on the results of the student response questionnaire to the predict-observe-explain (POE) oriented LKPD on energy sources material that was given to fourth grade students at SD Negeri Kuto Tanjung, the results obtained were 77.24% in the very good category. Predict-observe-explain (POE) oriented worksheets can improve students' higher- order thinking skills indicated by a standard gain value of 0.31 in the medium category.